THE BERKELEYAN CONCEPTION OF NATURE - Grzelinski, A. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The aim of the article is to show various meanings of nature in Berkeleyan philosophy: in his mechanic philosophy, optics, in his understanding of ether and the theory of beauty.